Do High Interest Rates Reduce Inflation? A Test of Monetary Faith - Blair Fix (Economics from the Top Down, 2023)
Whenever inflation rears its head, the call soon comes to raise interest rates. The rationale is simple. Higher interest rates put a damper on the supply of money. And this monetary clamp slows inflation. It's so intuitive that it must be true. Or is it? As the Reverend Brooke observes, it takes a person of true conviction to ignore apparent contradictions. As such, this post is designed to test your monetary faith. According to monetary orthodoxy, higher interest rates reduce inflation. Yet the evidence demonstrates that the opposite is true: higher interest rates are associated with higher inflation. With this evidence in mind, I invite you to read on. Put your monetary faith to the fire and see if it can survive.
Keywords: E43; E52; E31; E4; 330; interest rate; inflation; Milton Friedman; monetarism; monetary policy